A comprehensive approach to single and double line contingency screening. Issue 5 (5th September 2016) - Montagna, Mario
Abstract : Purpose: The purpose of this paper is to show some techniques to perform line contingency screening efficiently. Design/methodology/approach: Computation efficiency and speed are mandatory requirements of contingency screening, especially when multiple outages need to be considered. The classical bounding principle, i.e. the idea that the effects of an outage are restricted to the area where the outage occurs, becomes increasingly difficult to apply to multiple contingencies. In the present work a comprehensive strategy, based on a systematic elimination of non-dangerous outages, is shown to be easily applicable to both single and double contingencies. Findings: Tests show the efficiency of the proposed methods with reference to test systems and to an actual network with up to 800 buses. Originality/value: The bounding approach is the basis of most efficient contingency screening methods based on the linear dc load flow model. In the present work the method is re-considered to improve computational efficiency. The symmetry of the dc Jacobian and the sparse inverse technique are suitably exploited in the evaluation of line outage distribution factors; this also allows a combination of single and double line contingency screening into a single procedure.